The Translators’ Background Impact on the Translation of the Noble Quran - Asst. Prof. Osama H Ibrahim (مجلة النور للدراسات الانسانية)
The current study delves into a significant topic, namely, the background knowledge impact that affects the quality of translation of the translated verses under study. It examines the extent to which the translators of the noble Quran intervene in the translation process with their ideological background. It is hypothesized that once the translator inculcates his background knowledge (whether religious or social ideology), the quality of the translation product is a result of managing rather than monitoring. Being the case so, they add, alter, or delete some lexical items while translating the Quran. Five verses along with four translations constitute the data of this study. After an insightful interpretation and analysis depending on the authentic books of exegesis, it became evident that some of the translations are managed by using ideologically biased words and phrases. Finally, it is highly recommended that these translations need to be revised in a way that reflects the intended meaning accurately and faithfully